The Quality of Distance Learning from an Economic Perspective: A Case Study from Hong Kong - Chan Chi Wai (Flexible Learning Association of New Zealand, 2011)
This paper examines the quality of distance education in terms of its impact on the earnings of workers, based on Hong Kong's 2001 census and 2006 by-census data. Education and training, which are an investment in human capital, enhance the productivity of workers and increase their lifetime incomes: a more productive investment will produce a higher rate of return. The effects of education and training on workers' earnings can be regarded as a proxy for measuring the quality of education undertaken. This study shows that, as regards earnings, and therefore (indirectly) quality, there is no statistically significant difference between distance and traditional education.